Variations in response control within at-risk gamblers and non-gambling controls explained by GABAergic inhibition in the motor cortex. (June 2018) - Chowdhury, Nahian S.; Livesey, Evan J.; Blaszczynski, Alex; Harris, Justin A.
Abstract: Paired-pulse Transcranial Magnetic Stimulation (TMS) is used to study inhibitory and excitatory mechanisms in the motor cortex through the measurement of short-interval intracortical inhibition (SICI), indicative of GABAergic activity, and intracortical facilitation (ICF), indicative of glutamatergic activity. In the present study, TMS was delivered to the left motor cortex of 40 participants while we measured SICI and ICF at rest. We were interested in whether variation between individuals in these modulatory mechanisms is related to inhibitory control over responding measured as stop signal reaction time (SSRT). Within the same group of participants, we investigated whether SICI, ICF, SSRT, and self-reported impulsivity, are impaired in participants identified as At-Risk gamblers (n = 20) compared to non-gambling controls (n = 20). We found a significant negative correlation between SICI strength and SSRT, but no correlation between ICF strength and SSRT after controlling for the correlation between SICI and SSRT. Thus, poor inhibitory control of responding was associated with weak GABAergic activity. When taking into account the effects of substance/alcohol use and attention-deficit hyperactivity disorder (ADHD) symptom severity, At-Risk gamblers showed elevated self-reported impulsivity, but did not differ from controls on SSRT or SICI/ICF. Our study is the first to show that individual differences in motor cortex inhibition can predict stopping performance, and the first to investigate paired-pulse TMS parameters (together with other impulse control measures) in a gambling population.